2021
DOI: 10.3390/ijms22031020
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Methylation Analysis Identifies Patterns in Progressive Glioma Grades to Predict Patient Survival

Abstract: DNA methylation is an epigenetic change to the genome that impacts gene activities without modification to the DNA sequence. Alteration in the methylation pattern is a naturally occurring event throughout the human life cycle which may result in the development of diseases such as cancer. In this study, we analyzed methylation data from The Cancer Genome Atlas, under the Lower-Grade Glioma (LGG) and Glioblastoma Multiforme (GBM) projects, to identify methylation markers that exhibit unique changes in DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 58 publications
(66 reference statements)
0
14
0
Order By: Relevance
“…This suggests that SMOC1 may act as a tumor suppressor. A recent study has analyzed the methylation data of the glioma project from the TCGA database and identified 10 glioma grade-associated cytosine-phosphate guanine sites, which targeted four genes, including SMOC1 (Weng and Salazar, 2021). Another in silico study identified a seven-gene signature, including SMOC1, which was positively correlated with 5-years OS of glioma patients (Zhang G.-H. et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that SMOC1 may act as a tumor suppressor. A recent study has analyzed the methylation data of the glioma project from the TCGA database and identified 10 glioma grade-associated cytosine-phosphate guanine sites, which targeted four genes, including SMOC1 (Weng and Salazar, 2021). Another in silico study identified a seven-gene signature, including SMOC1, which was positively correlated with 5-years OS of glioma patients (Zhang G.-H. et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 60 patient-derived GSC cultures indicated that stratification into distinct clusters based on epigenetic markers can predict patient survival, highlighting the prognostic influence of epigenetic regulation and heterogeneity across tumor samples [ 154 ]. Similarly, identification of methylation markers at CpG sites in GBM samples can predict tumor progression and overall survival [ 155 ].…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…The methylation of specific cytosine bases within gene promoter regions, coupled with the modification of associated histone proteins, comprises the epigenetic control of gene transcription. In glioblastoma, the aberrant hypermethylation of several genes, resulting in transcriptional silencing, is associated with poor patient prognosis [79]. Alternatively, the promoters of transforming genes can become hypomethylated, resulting in aberrantly increased gene expression.…”
Section: A Special Role For Methionine In Dna Methylationmentioning
confidence: 99%
“…The ANXA2 gene product is a positive regulator of the mesenchymal subtype, and loss of DNA methylation in the promoter of the ANXA2 gene can drive mesenchymal transformation [92]. Loss of methylation in promoters of other genes, such as uridine phosphorylase (UPP1), is also associated with decreased survival [79].…”
Section: Potential Consequences Of Methionine Restriction In Glioblas...mentioning
confidence: 99%